2011
DOI: 10.1002/jts.20627
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to suicidal behavior in posttraumatic stress disorder*

Abstract: This study investigated paths to suicidal behavior in 94 civilian participants with chronic posttraumatic stress disorder (PTSD). Two statistical modeling programs, TETRAD II version 2.1 and Mplus 5.21 were used to construct a working model of suicide in PTSD. Two paths to suicidal behavior were identified. In the first path, suicidal behavior was directly associated with greater life impairment, which in turn was associated with poorer occupational and social functioning. In the second path, suicidal behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…Most notably, although suicide prevention often focuses on the early detection of depression (e.g., Hegerl, Wittenburg, & the European Alliance Against Depression Consortium, 2009), suicidal behavior also can arise from a variety of other psychological states and conditions (e.g., Briere & Eadie, 2012;Fergusson, Woodward, & Horwood, 2000;Panagioti, Gooding, Dunn, & Tarrier, 2011;Sareen, 2011). The current study indicates that posttraumatic stress, specifically hyperarousal, may be an additional antecedent to suicidality.…”
Section: Discussionmentioning
confidence: 83%
“…Most notably, although suicide prevention often focuses on the early detection of depression (e.g., Hegerl, Wittenburg, & the European Alliance Against Depression Consortium, 2009), suicidal behavior also can arise from a variety of other psychological states and conditions (e.g., Briere & Eadie, 2012;Fergusson, Woodward, & Horwood, 2000;Panagioti, Gooding, Dunn, & Tarrier, 2011;Sareen, 2011). The current study indicates that posttraumatic stress, specifically hyperarousal, may be an additional antecedent to suicidality.…”
Section: Discussionmentioning
confidence: 83%
“…This therapeutic technique uses mental imagery to encourage individuals to recall positive memories in order to experience the positive emotional states associated with the memories (Tarrier, 2010). A preliminary test of this mood-boosting strategy found that it was effective in increasing both short-term hope and happiness in people with a diagnosis of schizophrenia (Johnson et al, 2013) and post-traumatic stress disorder (Panagioti et al, 2011). The present finding provides preliminary supportive evidence for the incorporation of such a memory-based selfmanagement strategy (i.e., reflecting on past positive social experiences when suicidal feelings occur) into psychological interventions which aim to target suicide risk in people with bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Other models highlight the role of various cognitive-affective processes as direct or indirect mediators between PTSD and suicidality, including perceptions of defeat and entrapment (e.g., [93]), negative self-appraisals (e.g., [94]), hopelessness (e.g., [91]), and guilt and shame (e.g., [95]). In addition, some models propose that the link between PTSD and suicidal behavior is partially explained and/or compounded by other comorbid problems such as functional impairment [96], depression [97], sleep disturbance [98], and alcohol dependence [99]. Taken together, these models suggest that treating PTSD is likely to reduce suicidality directly by reducing PTSD symptoms and indirectly by reducing established cognitive and affective mediators as well as other compounding problems.…”
Section: Suicidalitymentioning
confidence: 99%